(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The white wax scale, Ceroplastes destructor (Hemiptera: Coccidae), has become a common pest in some citrus orchards in the Western and Eastern Cape Provinces of South Africa over the past six to eight years. A study over three consecutive years on the biology of C. destructor and the seasonal abundance of its natural enemies indicated that there is a temporal synchrony between the population densities of the susceptible scale stages and some of its natural enemies, showing that the scale-natural enemy association contained a density-dependent regulatory mechanism. Parasitoids and predators acted as density-dependent mortality factors during the pre-ovipositing female stage. Bioassays of some of the insecticides commonly used for the control of red scale and false codling moth indicated that most are highly detrimental to one of the major parasitoids of C. destructor. This could represent one of the reasons for the increase in the distribution and densities of C. destructor over the past decade. Our study has also indicated that the sex ratio of Aprostocetus (= Tetrastichus) ceroplastae (Girault), a dominant primary endo-parasitoid of C. destructor, reared from early third-instar was male-biased while that of parasitoids reared from mature adult female was slightly female-biased. The implication of this for a possible mass rearing of A. ceroplastae and biocontrol of C. destructor is discussed.